Husband Support on BOM Massage Practice and Reducing Fatigue in Post Partum Mothers - Umarianti, Tresia; Putriningrum, Rahajeng; Prasetyoningsih, Aris; Prasetyo, Budi (Journal of Maternal and Child Health, 2021)
Background: BOM massage is a combination of ways to treat breasts so that breast milk can produce and provide relaxation to postpartum mothers. Mothers after giving birth may experience psychological fatigue related to anxiety or depression which can hinder the smooth flow of breast milk. The support of the husband and close family will greatly help the process of comfort and relaxation of the mother during the process of undergoing the postpartum period. This study aims to determine the effect of husband's assistance in the implementation of BOM messages on the level of fatigue of postpartum mothers. Subjects and Method: This research is an analytic experimental study with RCT (Randomized Controlled Trial) design. The research was conducted at PMB Ngudi Saras Palur Karanganyar. The research subjects were 44 postpartum mothers, which were divided into 22 with husband's assistance and 22 others without husband's assistance. The sampling method is purposive sampling. Data were analyzed using independent-sample t-test. Results: Fatigue test results in the intervention group were lower (Mean= 2.82; SD= 1.05) compared to the control group (Mean= 7.14; SD= 1.04). Statistical test Independent-Sample T-test has an effect size of 4.13 and there is an effect with a p<0.001. Conclusion: Husband's assistance in the implementation of BOM Massage has an effect on the level of fatigue of postpartum mothers in Palur Karanganyar.